Recent Advances of Aminopyrimidines in Multicomponent Reactions - Bharti, Ruchi; Kumari, Pooja; Parvin, Tasneem; Choudhury, Lokman H. (Current Organic Chemistry, 2018)
Background: Aminopyrimidines represent very important class of functionalized heterocycles having wide applications in organic and medicinal chemistry. Recently, considerable attention has been paid on exploration of aminopyrimidines in pot, atom and step economic multicomponent reactions. Objective: The main objective of this review is to give an overview on the recent applications of aminopyrimidines in multicomponent reactions. Method: In this review, we have broadly divided all the aminopyrimidine based multicomponent reactions into two major categories leading to (i) cyclic pyrimidine fused derivatives and (ii) acyclic substituted pyrimidine derivatives as products. Again reactions forming fused heterocycles from the aminopyrimidine based multicomponent reactions have been sub categorized as MCRs providing five membered, six membered and spirofused products. Similarly, MCRs providing acyclic substituted products have been subdivided into two categories involving only C-nucleophilic site of the aminopyrimidine to give C-substituted aminopyrimidines and using N-nucleophilic site to provide N-substituted acyclic products. Conclusion: We have shown the various reactivity patterns of aminopyrimidines in multicomponent reactions and up-to-date literature on aminopyrimidine based MCRs has been systematically presented. Finally, aminopyrimidines are considered as promising substrates in MCRs for the synthesis of diverse heterocycles. We hope that this review will serve as a stimulus for ongoing research in the field of MCRs and heterocyclic chemistry.
Keywords: dihydropyridopyrimidines